Dental caries and its associated factors among children aged 8-12 years in Libyan schools, Klang Valley, Malaysia - Abdullah Abuaisha, Aisha Ageil; Zainuddin, Huda (Life Sciences Society of Pakistan, 2018)
Background: Dental caries is a serious public health problem worldwide. Prevalence of dental caries among school children has increased in both developed and developing countries since the last few decades. Objective: To determine the association of dental caries with socio demographic factors among Libyan school children aged 8-12 years in Klang Valley, Malaysia. Methods: A cross-sectional study was conducted in three Libyan primary schools in Klang Valley, Malaysia. Five hundred and seventy children aged 8-12 years participated. They were randomly selected using proportional stratified sampling method. Dental caries was assessed using the WHO (1987) criteria. Results: Response rate was 92.5%. The prevalence of dental caries was (55.8%), females have higher dental caries than males. Dental caries was found highly prevalent among; children their aged ≤10 years (64.7%), children whose father and mother have a job (58.5% and 58.7%) respectively, children whose father and mother have elementary level of education (69.6% and 61.0%) respectively. Chi square test showed significant association of dental caries with age group and father’s education level. Logistic regression analysis identified young age (OR=11.78, 95% Cl: 2.305 -26.276) was significant predictor of dental caries among children. Conclusions: Younger children are at higher risk of having dental caries in this study. Health education should be emphasized among younger Libyan school children.